Healthy Nutrition in Current Scientific Research - Savas, Hasan Basri (Turkey Health Literacy Journal, 2022)
Nutrition is one of the controllable factors for a healthy life. For this reason, information on healthy eating is increasingly in the interest of health professionals. In addition, the importance of healthy nutrition is increasing more in preventive medicine recommendations and treatment guidelines against diseases. It is of great importance for both patients and physicians to follow up-to-date information on healthy nutrition. In this study, it is aimed to show the concepts of correct meal frequency and calorie restriction regarding healthy nutrition by examining current scientific researches. According to current current evidence, to eat healthy; to reduce the frequency of meals, if possible, to eat two meals a day, late in the morning and early in the evening, to collect all calorie intake in two meals by removing snacks, to keep the daily calorie needs calculated according to individual needs under control, to apply calorie restriction to prevent calorie excess, in order to protect from the negative effects of the restriction, it will be useful to apply a moderate calorie restriction that includes around 20% daily calorie restriction.
Keywords: Healthy nutrition, meal frequency, calorie restriction, preventive medicine.